Guía para la Elaboración del Estado de Flujo de Efectivo según NIIF para PYMES: Método Directo e Indirecto - Román Urbano, Dayanna Katherine (2022)
Small and medium-sized companies are searching to ensure their survival and competitiveness in domestic and international markets. To support strategic decision-making based on traditional financial statements, and the cash flow statement. Currently, this financial statement is essential to evaluate the source of cash and cash equivalents. According to financial information specialists, preparing the cash flow statement is a challenge due to the degree of complexity and resources required for its preparation; therefore, the objective of the research is to provide a support guide to prepare the cash flow statement by the direct and indirect method, according to the international standards that regulate the SME sector. We undertook a non-experimental qualitative study with a descriptive approach, using observation and documentary review techniques; we selected a non-probabilistic sample by convenience under the criteria of proximity, sector, and amount of assets. The procedure described in the guide for the direct methodology is more complex than for the indirect method. Its presentation is in gross terms; the indirect method, on the other hand, does not require more detail; its submission is in net terms, and both methodologies provide quality, understandable and reasonable financial information, so neither method is better than the other one, the choice of method responds to the objectives and policies of the company. The preparation of the cash flow statement provides multiple advantages for SMEs, such as the ease of obtaining financing, proper cash management in planning, financial control, and increased productivity. In addition, its analysis with the rest of the financial statements provides a complete picture of the economic and financial reality of the SMEs.